The Effects of Suspended Particulate Matter, Nutrient, and Salinity on the Growth of Amphidinium carterae Under Estuary Environmental Conditions - Jiang, Zong-Pei; Tong, Yuqi; Tong, Mengmeng; Yuan, Jiajun; Cao, Qin; Pan, Yiwen (Frontiers in Marine Science, 2021)
The environmental conditions in estuaries display distinct variability along the river-ocean mixing continuum from turbid, eutrophic freshwater to clear, oligotrophic offshore oceanic water. In order to understand the effects of suspended particulate matter (SPM), nutrient, and salinity on phytoplankton growth, this study investigated the response of a harmful dinoflagellate (Amphidinium carterae Hulburt) to the ecological gradients in estuary environments. Rapid nutrient uptake and growth of A. carterae were detected in the nutrient-rich clear water, while nutrient concentration had little impact on the cellular chlorophyll a (Chl-a) content at the stationary phase. Light attenuation caused by SPM not only inhibited the specific growth rate of A. carterae but also prolonged its adaption period in turbid water, resulting in a delayed and weakened growth response. The elevated cellular Chl-a content under high SPM conditions resulting from photo-acclimation led to the decoupling of cell density and Chl-a concentration, indicating that Chl-a is not a reliable indicator for phytoplankton abundance in turbid environments. The combined effect of SPM and nutrient on specific growth rate of A. carterae can be explained by the comparative effect model, while the multiplicative effect model better predicted their interactive effect on the growth inhibitory rate (GIR). There is a transit of dominant limiting factor for phytoplankton growth along the salinity gradient in estuary environments. Salinity (for marine phytoplankton cannot survive under low salinity condition) and SPM are the dominant limiting factors at low salinities in nearshore turbid environments, while nutrient depletion exerts the dominant inhibitory effect in high salinity offshore water. Depending on the balance between enhancing nutrient limitation and reducing light limitation with increasing salinity, blooms most likely occur in the “optimal growth region” at intermediate salinities where light and nutrient are both suitable for phytoplankton growth.